DAMPAK KREDIT PT. BANK PERKREDITAN RAKYAT (BPR) GANDA LATA TERHADAP PENDAPATAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KECAMATAN UNAAHA KABUPATEN KONAWE - Shalihuddin, Shalihuddin; Firman, Akhmad; Barani, La Ode Samsul (JURNAL EKONOMI UHO, 2016)
This study aimed to find out credit impact of BPR Ganda Lata for small traders of basic commodity in Unaaha District Konawe Regency. Data used in this study was primary and secondary data. Samples in this study were 21 respondents. Data analyzed through descriptive analysis, by compare condition of traders before and after receiving credit of BPR Ganda Lata. The result showed that the credit impact for small traders increased in revenue about 95.23% of respondent. The traders with 9 million rupiah of credit or below experienced increased in revenue monthly about 21,50 %; for traders with 10 - 19 million of credit increased in income about 17,45 %, and about 19,89% for traders with 20 - 29 million rupiah of credit. While respondents who took credit 40 - 50 million rupiah have average monthly incomes increased to 17,89 %.